Using NF-κκB as a molecular target for theranostics in radiation oncology research. (March 2012) - Liu, Yu-Chang; Chiang, I-Tsang; Hsu, Fei-Ting; Hwang, Jeng-Jong
Resistance of cancer cells to chemotherapy and/or radiotherapy is a major challenge to current anticancer treatment. The NF-κκB signaling pathway plays an important role in tumor development and progression, and results in unsatisfactory treatment outcome. Inhibition of the NF-κκB signaling cascade may sensitize the resistant cancer cells to chemotherapy and/or radiotherapy. Here, the correlation of NF-κκB molecules with carcinogenesis and tumor progression, along with its significance in clinical practice, is reviewed. The potential clinical application of NF-κκB and its associated molecules as diagnostic and therapeutic targets is also discussed.